TAFSIR AYAT-AYAT NEUROSAINS (‘Aql Dalam Al-Qur’an dan Relevansinya Terhadap Pengembangan Berpikir Kritis dalam Pendidikan Islam) - Muhammad Faiz Rofdli; Suyadi Suyadi (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2020)
Development of reason or innovative creative thinking in Islamic education so far has been seen as not having a normative and theological foundation in the Koran so that it is clashed with the development of morals that already have a normative basis in the Koran, namely qolb. This study analyzes the concept of ‘Aql in the Koran as a normative-theological foundation for critical, creative and innovative thinking in Islamic education. The approach in this study is a qualitative type of library research. The data source in this study is the interpretation of the Qur'anic verses about the activities of thinking or berpikir ‘Aql, such as thinking (fikr), pondering (taddabur), understanding (tabashshur), understanding and so forth. The data analysis technique used in this study is interpretive hermeneutics. Qur'anic verses about neuroscience can be traced through key terms that refer to brain activity. The results showed that the interpretation of neuroscience verses can be traced through the concepts of tafakur, tadabur, ta'aqul, and so on. The interpretation of the concept of ‘Aql in the perspective of neuroscience can be a theological normative foundation in the development of critical, creative and innovative thinking in Islamic education. the results of this study will have implications for the paradigm of Islamic education which was originally only oriented to developing dichotomic qolb-based morals into the development of the critical thinking potential of students who are more holistic with a more scientific approach.